2010
DOI: 10.1021/ic9022097
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin-Based, Electron-Trapping Iridium Complexes as Highly Efficient and Stable Phosphorescent Emitters for Organic Light-Emitting Diodes

Abstract: A new class of coumarin-based iridium tris-cyclometalated complexes has been developed. These complexes are highly emissive, with emission colors ranging from green to orange-red. Besides modification of ligand structures, color tuning was realized by incorporation of ligands with different electrochemical properties in a heteroleptic structure. The organic light-emitting diodes (OLEDs) using these compounds as emissive dopants are highly efficient and stable. Unlike other Ir(III) phosphorescent dopants, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…The synthesis and photophysical properties of (bppo) 2 Ir(ppy) and (ppy) 2 Ir(bppo) have been reported previously 31 . A reaction between [Ir(bppo) 2 (µ-Cl)] 2 and ppy-H formed both (bppo) 2 Ir(ppy) and (ppy) 2 Ir(bppo) in moderate yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis and photophysical properties of (bppo) 2 Ir(ppy) and (ppy) 2 Ir(bppo) have been reported previously 31 . A reaction between [Ir(bppo) 2 (µ-Cl)] 2 and ppy-H formed both (bppo) 2 Ir(ppy) and (ppy) 2 Ir(bppo) in moderate yield.…”
Section: Resultsmentioning
confidence: 99%
“…The collected fraction was precipitated from CH 2 Cl 2 and hexanes to yield 280 mg pure (bppo) 2 Ir(acac) (51%). 1 Iridium(III) bis(2-phenylpyridinate)(benzopyranopyridinone) ((ppy) 2 Ir(bppo)) and iridium(III) bis(benzopyranopyridinone) (2-phenylpyridinate) ((bppo) 2 Ir(ppy)) were synthesized by methods similar to those described in a previous report 31 Optical spectra. Ultraviolet-visible absorption spectra were recorded using a Hewlett-Packard 4853 diode array spectrometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The organic electroluminescent materials have been intensely applied in the past two decades [1][2][3]. In an organic light emitting diode (OLED) device, both singlet and triplet excitons are generated in about 1 to 3 ratio by charge recombination [2].…”
Section: Introductionmentioning
confidence: 99%
“…In OLED devices based on phosphorescent materials, both singlet and triplet excitons can be harvested for ligowing to intersystem crossing of the singlet excited states to the triplet states, 100% internal quantum efficiency can be obtained [10,11]. Highly efficient electrophosphorescent OLEDs have been reported by using Ir (III) complexes and Pt (II) complexes [10,12,13].The studies of coumarin derivatives demonstrated that they have super thermal stability and outstanding optical properties including an extended spectral response, high quantum yields, superior photostability [14][15][16][17][18][19][20][21][22][23][24][25]. Recently, we found that coumarin derivatives have a quantum yield of photoluminescence larger than 50% and good electroluminescence properties [16][17][18][19][20][21].…”
mentioning
confidence: 99%